Effect of Heartfulness meditation program on perceived stress and satisfaction with life of female students - Gupta, Pradeep K; Malhotra, Neetu; Goel, Preeti; Thimmapuram, Jayaram; Krishna, Prasanna (Frontiers in Psychiatry, 2023)
Though literacy levels are slowly improving in India due to the steps taken by the Government of India, it has been a challenge for female students with gender disparities in literacy levels. Stress levels are high in students, more so during their exam times. While prior literature has demonstrated the prevalence of stress during student life, there is limited evidence of any interventions to decrease stress and improve satisfaction with life, specifically for female students. Heartfulness meditation is a heart-based meditation practice that may reduce stress and improve satisfaction with life among female students. We conducted a prospective cohort analysis comparing perceived stress and satisfaction with life outcomes among female students who self-selected to participate in the Heartfulness meditation program. The first group, G20, underwent intervention from week 0 until week 12 and continued their practice independently until week 20. The second group, G14, joined the intervention from week seven until week 12 with only a six-week exposure to guided meditation sessions through Heartfulness Trainers. They continued their practice independently until week 20. Data on Perceived Stress (PSS) and Satisfaction with Life (SWLS) were collected at week 0 and week 20 for both groups. G20 had 127 participants, and G14 had 113 participants. Ninety-four participants from the G20 group and 93 from G14 completed the study. The G20 group showed a statistically significant reduction of PSS scores from 20.79 to 18.96, and an increase in the SWLS scores from 22.03 to 23.51 from baseline to the end of the study period. The study of the Pearson correlation coefficient indicated that there is a weak positive correlation between pre- and post-scores for both the groups for both PSS and SWLS. Our findings suggest that Heartfulness meditation practice offers significant benefits with perceived stress and satisfaction with life among female students independent of their age. Still, a prolonged guided intervention of over six weeks is needed. A larger, randomized study with an additional control group with no meditation intervention is recommended.